Republic of Kosovo : 2021 Article IV Consultation-Press Release and Staff Report. (IMF Staff Country Reports; Country Report ;, 2022)
After contracting more than 5 percent in 2020, Kosovo's economy is projected to have recovered by 7.5 percent in 2021, thanks to mobility normalization, extraordinary diaspora inflows, and strengthened confidence. Improved vaccination rates supported these trends and mitigation and recovery measures provided lifelines to those most affected by the pandemic. Though GDP growth is expected to normalize in 2022, the new omicron variant is a reminder that the pandemic continues to represent the main downside risk.